Identifikasi Formalin Pada Buah Import (Apel) Yang Diperjualbelikan Di Kota Makassar - Mega Lestari; Bakri Umar; Ardiansah Hasin (Jurnal Media Laboran, 2018)
Formalin is an organic mixture known as aldehyde. Formallin is known as formaldehyde with the CH2O chemical formula. Formalin is very dangerous if ingested and the consequences can cause cancer in humans. Formalin is usually added to the fruit for decay by traders. This study aims to determine whether or not there is formalin in imported fruit (Apple) which is traded in the city of Makassar. This type of research was conducted with descriptive laboratory observation. Qualitative tests of 3 Imported fruit samples (apples) taken by purposive sampling were tested using Chromatofat Acid reagent and obtained the results of all negative samples.